Microbial fuel cell-based biosensor for toxicity testing of Cr6+ - Cetinkaya, Afsin Y.; Ozkaya, Bestami (INDERSCIENCE ENTERPRISES LTD, 2019)
Water scarcity is one of the major challenges facing many communities in the 21st century and will become one of the most sensitive environmental matters in the next decade. Diversified chemical and biological tracing analyses are used to check the state and quality of superior quality drinkable water. But, these technologies are facing several difficulties, such as high costs, complex operating system, on-site and online restrictions. The latest techniques in the use of microbial fuel cell (MFC)-based biosensors has an extraordinary possible for fast and real-time tracing of water supply quality. MFC-based biosensor can perform self-sustaining observing without additional transducers or power supplies. MFC-based sensor technology ha also been investigated to remove different toxic compounds and to determine the availability of toxic compounds in the wastewater. In this study, the effect of different concentrations of Cr (VI) on MFC based-biosensor was investigated. It is seen that 2 mg/L Cr (VI) does not cause a serious change in system performance. It has been observed that electricity production capacity has changed in different Cr (VI) constructions.
Keywords: toxicity; biosensor; water treatment; POWER-GENERATION; BIOFILM; SENSOR; REMOVAL; IMPACT; BOD; Environmental Sciences & Ecology